Genetic Susceptibility to Antisynthetase Syndrome Associated With Single-Nucleotide Variants in the IL1B Gene That Lead Variation in IL-1β Serum Levels - Ponce-Gallegos, Marco Antonio; Ramos-Martínez, Espiridión; García-Carmona, Adriana; Mejía, Mayra; Nava-Quiroz, Karol J.; Pérez-Rubio, Gloria; Ambrocio-Ortiz, Enrique; González-Pérez, Montserrat I.; Buendía-Roldán, Ivette; Rojas-Serrano, Jorge; Falfán-Valencia, Ramcés (Frontiers in Medicine, 2020)
The antisynthetase syndrome (ASSD) is an autoimmune disorder characterized by myositis, arthritis, mechanic’s hands, fever, Raynaud´s phenomenon, and interstitial lung disease. We aimed to evaluate SNPs in the IL1B gene and their association between ILD with antisynthetase autoantibodies, as well as IL-1β serum levels. The most frequent antisynthetase autoantibody was anti-Jo1. The most frequent tomographic pattern was NSIP, while in the anti-Jo1 subjects, it was OP. Anti-Jo1 patients tend to have more significant arthritis, Raynaud’s phenomenon and have higher levels of CPK. In the IL1B gene, the GG genotype and G allele of rs1143634 (OR = 2.21 and OR = 2.60, respectively, p<0.05) are associated with an increased risk, as well as with the dominant and recessive models (p<0.05). This finding is maintained after logistic regression analysis adjusting by potential confounding variables (p<0.05). Subjects with the rs16944/AG heterozygous genotype had higher serum levels of IL-1 compared to homozygous (p<0.05). In conclusion, rs1143634 is associated with a higher risk of ASSD. Also, and the GA genotype is associated with higher levels of IL-1β in ASSD patients.